Pendampingan Penggunaan Reference Management Software dalam Penyusunan Jurnal dan Karya Ilmiah - Ulum, Miftachul; Mun'im, Abdul (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This community assistance activity aims to provide assistance to lecturers and academics in compiling scientific papers and journals using reference management applications. This service method is carried out with assistance and training using the Mendeley Desktop application. The activity was held on February 14 2021, attended by 40 lecturers. The results of the research show that using Mendeley is very helpful in the process of writing journals and scientific work. Participants are very enthusiastic about participating in this activity and it is very important for the activity to be carried out.